2022
DOI: 10.1021/acs.joc.2c01063
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Synthesis of Spiro-dihydropyridine Oxindoles via Cascade Spiro-cyclization of Knoevenagel/Aza-Michael Adducts

Abstract: An efficient, straightforward, and one-pot synthesis of biologically relevant spiro-dihydropyridine oxindoles was described via readily available isatin, malononitrile, allenoate, and amines. The metal/organocatalyst-free, Et 3 N-mediated reaction proceeds via cascade spiro-cyclization of in situ generated Knoevenagel/aza-Michael adducts. The reaction has great flexibility over electron-rich and electron-poor substituents affording desired products in good to excellent yields. We have also demonstrated the sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Therefore, many effective methods have been developed to synthesize spiro compounds . In general, isatin, due to the important reactivity of the 3-position carbonyl group, is one of the basic reagents for the construction of spiro compounds . Studies have shown that isatins generally maintain their structural integrity during this transformation (Scheme , a).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many effective methods have been developed to synthesize spiro compounds . In general, isatin, due to the important reactivity of the 3-position carbonyl group, is one of the basic reagents for the construction of spiro compounds . Studies have shown that isatins generally maintain their structural integrity during this transformation (Scheme , a).…”
Section: Introductionmentioning
confidence: 99%